The Role of Faith in Overcoming Challenges During Crisis: A Narrative Inquiry - Hendriks, Alvyn Cesarianto; Hendriks, Anne Lou M. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Though crises arise, supporting students are still determined to attend a tertiary institution to continue and finish their education. Without financial assistance, these supporting students rely on a kind of faith that enables them to sustain and attain success despite the challenges and struggles they face. This narrative inquiry documents students’ lived experiences. It highlights how they face life with positivity and enthusiasm. Findings revealed that their kind of faith made them overcome the different challenges they have. These implied that no matter how difficult life is, faith is more than enough to assist. How to have faith and where to anchor one’s faith can be implications for further study. Keywords : Faith, challenges, crisis, narrative inquiry